Evaluation of Construction Site Noise to Allow the Optimisation of Construction Processes and Construction Machinery Selection - Radka Kantová (Applied Sciences, 2021)
During the pre-construction phase of an investment project, a construction plan is usually prepared by the building contractor. It contains financial plans, schedules, technical regulations with working procedures and proposals for the deployment of construction machinery and work teams. These items are then optimised in order to save money, shorten construction time and increase the quality of the final work while ensuring environmental and safety standards are maintained at the site. The ecological aspects of building work include compliance with the hygiene limits for building site noise, which is caused in particular by the simultaneous operation of machines. In the Czech Republic, limit values are set by Government Regulation 272/2011 Coll., as amended, on the protection of health against the adverse effects of noise and vibrations. The evaluation of construction site noise is not usually performed by contractors themselves and noise is usually measured only at the construction site, where work is limited or additional measures are taken in the case of values that exceed the stipulated limits. As the values in the construction plan should be as close as possible to reality during the implementation of the plan, it would seem appropriate to include such noise assessments within it. The purpose of this paper is to present an example of such an evaluation from the formal and material standpoint. The assessment has been conducted in the form of a specific noise study, expanded by a commentary on the treatment of the hypotheses. It shows how to obtain input data for evaluation, divide sub-calculations and use the supporting SW of the Hluk plus product for the purposes of construction information modelling, as well as how to correctly set noise sources and the positions of measured points for evaluation by the model within this programme. Subsequently, options for the evaluation of appropriate measures are listed, including their inclusion in reassessments.